Micro Trojan horses: Engineering extracellular vesicles crossing biological barriers for drug delivery - Bin Zeng; Ying Li; Jiang Xia; Yin Xiao; Nawaz Khan; Bin Jiang; Yujie Liang; Li Duan (Wiley, 2024)
Abstract The biological barriers of the body, such as the blood-brain, placental, intestinal, skin, and air‐blood, protect against invading viruses and bacteria while providing necessary physical support. However, these barriers also hinder the delivery of drugs to target tissues, reducing their therapeutic efficacy. Extracellular vesicles (EVs), nanostructures with a diameter ranging from 30 nm to 10 μm secreted by cells, offer a potential solution to this challenge. These natural vesicles can effectively pass through various biological barriers, facilitating intercellular communication. As a result, artificially engineered EVs that mimic or are superior to the natural ones have emerged as a promising drug delivery vehicle, capable of delivering drugs to almost any body part to treat various diseases. This review first provides an overview of the formation and cross‐species uptake of natural EVs from different organisms, including animals, plants, and bacteria. Later, it explores the current clinical applications, perspectives, and challenges associated with using engineered EVs as a drug delivery platform. Finally, it aims to inspire further research to help bioengineered EVs effectively cross biological barriers to treat diseases.